IL‐32α has differential effects on proliferation and apoptosis of human melanoma cell lines. Issue 4 (12th January 2016) - Nicholl, Michael B.; Chen, Xuhui; Qin, Chenglu; Bai, Qian; Zhu, Ziwen; Davis, Matthew R.; Fang, Yujiang
Abstract : Background: Interleukin‐32 (IL‐32) is a recently recognized intracellular, proinflammatory cytokine which may play a role in cancer metastasis and patient survival. The role of IL‐32 in cancer, especially its direct effect on cancer cells, is not well understood. Material and Methods: Clonogenic assay, PCNA staining, Quick Cell Proliferation assay, TUNEL staining, and caspase‐3 activity assay were used to investigate the in vitro role for IL‐32α in human melanoma growth. We further investigated the possible molecular mechanisms using RT‐PCR and immunohistochemical staining. Results: Exogenous administration of IL‐32α inhibited proliferation of the HTB‐72 human melanoma cell line, but had little effect on other melanoma cell lines. Inhibition of proliferation in HTB‐72 correlated with increased expression of p21 and p53. IL‐32α administration also increased apoptosis in HTB‐72. This finding correlated with increased expression of TRAILR1. Conclusions: The data presented suggest a direct effect of IL‐32α on the growth of human melanoma and give some insight into the mechanisms which may in part govern this effect. J. Surg. Oncol. 2016;113:364–369 . © 2016 Wiley Periodicals, Inc.